Knowledge, attitude and practices of registered student nurse midwives towards utilization of internet and social media to obtain study materials in selected nursing schools of Zambia - Mafulauzi, Evaristo (Lusaka: University of Zambia , School of Medicine, 2015)
The internet is an important source of up-to-date medical information. Many people regularly use social networking sites such as Facebook and Twitter. Although several studies in different countries have explored the extent to which nursing schools use the computer and the internet there are researches available on this subject in Zambia. The purpose of this study was to determine knowledge, attitude and practices of registered student nurse midwives towards utilization of internet and social media to obtain study materials in selected nursing and midwifery schools of Zambia.
A study submitted in partial fullfilment of the requirements for the award of a Bachelor of Science Degree in Nursing.
Includes bibliographical references.
Keywords: Students--Zambia.; Internet users--Zambia.; Education, Nursing